A study to assess interobserver agreement for measuring the intraocular pressure using Goldmann applanation tonometry by two ophthalmologists - Dubey, Harshita; Shakya, Devendra Kumar; Rana, Divya; Shukla, Durgesh (Asian Journal of Medical Sciences, 2023)
Background: Precise use of Goldmann applanation tonometry (GAT) in the measurement of intraocular pressure (IOP) requires significant training since inaccuracies are common in the hands of untrained ophthalmic observer. Aims and Objectives: This study was conducted with the objective to measure interobserver agreement between two ophthalmologists in measuring the IOP using GAT in suspected glaucoma patients. Materials and Methods: This prospective observational study evaluated the agreement between the two observers for the measurement of the IOP using the GAT. The observers recorded IOP readings for 100 patients during two visits; both right and left eyes of the patients were examined during these visits. Pearson’s correlation coefficient, intraclass correlation coefficient (ICC), and Bland–Altman plot were used to interpretate the results as statistical measure. A P<0.05 was considered significant. All statistical analyses were performed using the Statistical Package for the Social Sciences. Results: In the present study, 100 subjects were examined for measuring the IOP using GAT. The range of the study subjects varies from 32 to 83 years. ICC (95% CI) values were more than 0.9, indicating excellent intraobserver reliability of the two observers. A fair correlation (r>0.90) was observed among the two observers. The agreement limit for the right eye and left eye during the first visit was (2.68, −2.18) and (2.32, −2.38), respectively. Agreement limit for the right eye and left eye during the second visit was (2.73, −2.11) and (1.83, −2.36), respectively. Conclusion: On seeing the Bland–Altman plot, it was found that there was excellent agreement between observers 1 and 2 since mostly observation lie within μ±1.96*σ. Since there was fine agreement found between the two trained observers. This indicates proper training of opthmalogosists can increase the precision in measuring IOP using GAT.